0588 Relationship Between Congestive Heart Failure and Poor Sleep Quality in the US Population. (25th May 2022) - Blethen, Caroline; Mason, Brooke; Wills, Chloe; Killgore, William; Grandner, Michael
Abstract: Introduction: Few recent, population-level datasets have explored the relationship between congestive heart failure (CHF) and sleep difficulties. Methods: The 2017 - March 2020 data from the National Health and Nutrition Examination Survey (NHANES) were used. Sleep difficulties were self-reported as difficulties "falling asleep, staying asleep, or sleeping too much" within the previous two weeks, categorized as "never, " "less than half the days, " "more than half the days, " and "nearly every day." Sleep duration was self-reported and categorized as normal (6.5-8.5h), short (<6.5h), and long (>8.5h). A modified STOP-BANG score was created based on NHANES measures of snoring, daytime tiredness, snorting/gasping during sleep, hypertension, body mass index, age, and gender (no measure of neck circumference). Covariates included sex, age, race/ethnicity, education, and relationship status. Analyses were unweighted, with weighted results forthcoming. Results: Those who reported sleep difficulties more than half the days (OR: 1.78, [1.20, 2.65], p=0.004) and nearly every day (OR: 2.76, [2.01, 3.78], p<0.001) were more likely to also report a history of CHF, relative to those without sleep difficulties. After adjusting for covariates these relationships were maintained for those who reported sleep difficulties more than half the days (OR: 1.71, [1.14, 2.58], p=0.010) and nearly every day (OR: 2.45, [1.76, 3.41] p<0.001). When adding sleep duration category as a covariate (normal, short, or long sleep), those diagnosed with CHF were more likely to have sleep problems nearly every day (OR: 2.21, [1.38, 3.25], p<0.001). Those diagnosed with CHF are also likely to have a high risk for OSA (OR: 1.67, [1.39, 1.95], p<0.001). Conclusion: Poor sleep quality is associated with history of CHF, independent of sleep duration. CHF is also associated with population-level sleep apnea risk. Screening for sleep disorders (insomnia and/or sleep apnea) in CHF patients may improve outcomes. Support (If Any):